MICROSATELLITE GENETIC VARIATION IN CULTURED POPULATIONS OF AFRICAN CATFISH (Clarias gariepinus) IN INDONESIA - Imron Imron; Dadan Sunandar; Evi Tahapari (Indonesian Aquaculture Journal, 2011)
African catfish, Clarias gariepinus, is one of economically important farmed species in Indonesia. To support the development of aquaculture industry, high genetic quality of both broodstock and seeds is required and breeding program is considered as viable option. Information on genetic variation of the populations being considered to form a base population may give insight toward the appropriate strategy to be implemented in breeding program. This study was aimed to assess genetic variation in farmed populations of catfish in Indonesia using microsatellite markers with special emphasis on their use to develop breeding program. Three populations of farmed catfish, namely Dumbo, Paiton, and Sangkuriang were collected. Fifteen individuals representing each population were screened for microsatellite variability using seven primer sets (cga01, cga02, cga03, cga05, cga06, cga09, cga10). Results found that with exception of two loci (cga01 and cg02) which had a slight increase, the other four loci showed reduction in the number of alleles ranging from 35% to 80% depending on loci. Farmed populations also showed heterozygote deficient and inbreeding level, being the highest was found in Sangkuriang and the least was observed in Dumbo population. Individuals within populations contributed most (95%) while interpopulation variation accounted for only 5% of the total genetic variation. Populations of Dumbo and Sangkuriang were genetically similar while populations of Paiton were genetically different from both Dumbo and Sangkuriang. Viewed from genetic perspective, by combining all information emerging from this study, the best possible strategy to establish a base population with broad genetic base and less inbreeding would be to combine all the populations into a synthetic base population.